Les études à l'étranger des juristes brésiliens - Fabiano Engelmann (Les éditions de la Maison des sciences de l'Homme, 2009)
The present text constitutes an exploration of the profile of foreign studies of brazilian master's and doctoral professors of law, based on the information supplied in the data registered in CNPq's lattes platform in 2006. These data are analyzed in the context of the quarrel on the effect of internationalization of management expertise of State and uses of social sciences. In this direction, it can be constructed hypotheses on the relation of the international circulation of Brazilian jurists and the movements of importation and exportation of institutional models and its repercussion in the national legal and political space.